Pazopanib alleviates neuroinflammation and protects dopaminergic neurons in LPS-stimulated mouse model by inhibiting MEK4-JNK-AP-1 pathway - Sun Hong-yang; Wu Jin; Wang Rui; Zhang Shun; Xu Hao; Kaznacheyeva Еlena; Lu Xiao-jun; Ren Hai-gang; Wang Guang-hui (Acta Pharmacologica Sinica; Vol 44, No 6 (June 2023): Acta Pharmacologica Sinica, 2023)
Parkinson’s disease (PD) is a progressive neurodegenerative disease characterized by the loss of dopaminergic (DA) neurons and the accumulation of Lewy bodies (LB) in the substantia nigra (SN). Evidence shows that microglia-mediated neuroinflammation plays a key role in PD pathogenesis. Using TNF-α as an indicator for microglial activation, we established a cellular model to screen compounds that could inhibit neuroinflammation. From 2471 compounds in a small molecular compound library composed of FDA-approved drugs, we found 77 candidates with a significant anti-inflammatory effect. In this study, we further characterized pazopanib, a pan-VEGF receptor tyrosine kinase inhibitor (that was approved by the FDA for the treatment of advanced renal cell carcinoma and advanced soft tissue sarcoma). We showed that pretreatment with pazopanib (1, 5, 10 μM) dose-dependently suppressed LPS-induced BV2 cell activation evidenced by inhibiting the transcription of proinflammatory factors iNOS, COX2, Il-1β, and Il-6 through the MEK4-JNK-AP-1 pathway. The conditioned medium from LPS-treated microglia caused mouse DA neuronal MES23.5 cell damage, which was greatly attenuated by pretreatment of the microglia with pazopanib. We established an LPS- stimulated mouse model by stereotactic injection of LPS into mouse substantia nigra. Administration of pazopanib (10 mg·kg-1·d-1, i.p., for 10 days) exerted significant anti-inflammatory and neuronal protective effects, and improved motor abilities impaired by LPS in the mice. Together, we discover a promising candidate compound for anti-neuroinflammation and provide a potential repositioning of pazopanib in the treatment of PD.